Similaridade na diversidade funcional e composição de espécies de aves florestais entre duas planícies alagáveis e o planalto adjacente. - Ponço, Jhonatan Vicente (2016)
The floodplains studied are similar environments in some ways as the occurrence of remnants or forest patches, seasonal waterlogging, plant training. However, because they are geographically distant from each other, they should present compositions different bird species. However, the study plateau is geographically close to one of the plains, which suggests high similarity in the composition of bird species. This study seeks to analyze if both plains have similar functional diversity of values and also the composition of bird species is similar between the plains and plateau. Abundance data were used of birds using the method points at three sampling sites with three samples at each sampling site. We used three facets of the functional diversity (FD) (functional Wealth, Equitability functional and functional divergence) along with a PCoA. There was no difference between FD for the three sampling sites, but when evaluated the functional groups were separately difference between the plains, the Pantanal, and Plateau for herbivores. The PCOA showed differences in species composition separating Pantanal from other areas. This suggests that the ecological functions of bird communities are being provided in a similar manner in a wide geographical range and under abiotic and biotic conditions very different. The differences between the functional groups and the composition of species is mainly due to the colonization of the environment, life history and possibly hunting pressure for herbivores.